Effectiveness of the Problem Based Learning (PBL) Model in Improving the Mathematical Problem-Solving Ability of 5th Grade Elementary School Students in the Selayar Islands - Karmila Karmila; Patahuddin Patahuddin; Suryadi Ishak (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) model in improving the mathematical problem-solving abilities of fifth-grade elementary school students in the Selayar Islands. The research uses a quantitative approach with a quasi-experimental design thru a pretest-posttest control group design. The research sample consisted of 52 students, comprising 26 students in the experimental class and 26 students in the control class. The research instrument is a mathematics problem-solving ability test that has been tested for validity and reliability. Data were analyzed using an independent sample t-test and N-Gain test to determine the difference in the improvement of students' problem-solving abilities in both groups. The research results show that the average posttest score of the experimental class was 82.35, higher than the control class at 71.12. The t-test results indicated a significance value of 0.000 (<0.05), which means there is a significant difference in the improvement of mathematical problem-solving abilities between the two groups. In addition, the average N-Gain score of the experimental class was 0.72, which falls into the high category, while the control class had an average N-Gain score of 0.45, which falls into the moderate category. Thus, the Problem Based Learning model has proven effective in improving the mathematical problem-solving abilities of fifth-grade elementary school students in the Selayar Islands